Existence of solutions to non-local uncertain differential equations under the ψ-Caputo fractional derivative - Fouad Ibrahim Abdou Amir; Aziz El Ghazouani; M’hamed El Omari; Said Melliani (Miskolc Mathematical Notes)
In this manuscript, we look into the existence of solutions to a class of uncertain differential equations with non-local derivatives. The method relies on the Krasnosel’skii fixed point theorem as well as a lengthened Schauder fixed point theorem that is applicable on fuzzy metric spaces. This theorems implies that the topic in question has a fuzzy solution specified on a certain interval. Our strategy requires considering a linked integral problem wherein the aforementioned tools apply. We’ll wrap off with a physical incentive.